Assessing sustainability in smallholder vegetable farms in Benin Republic: A matrix approach - Fassinou Hotegni, Nicodeme V.; Nouhougan Alexandre Guidimadjègbè; Ayenan, Mathieu A.T.; Singh, Ravi Gopal; Odjo, Sylvanus (Elsevier, 2024)
This study aims to assess the level of sustainability in vegetable-based agrifood production systems in Benin and to propose actions to enhance sustainability, food safety, and year-round production in the vegetable production systems. Semi-structured interviews were conducted with 200 vegetable farmers in contrasting agroecological areas (with areas of extensive production of staples and intensive production of vegetables), using the “Indicateur de Durabilité des Exploitations Agricoles” (IDEA) framework (an on-farm sustainability index). Most of the surveyed vegetable farmers produced a wide range of crops, including leafy vegetables (amaranth, African eggplant, and African basil) and peppers, grown by more than 50% of the farmers. The average scores achieved by the vegetable farms regarding three dimensions of sustainability—ecological, social, and economic—were 35, 41, and 63, respectively, out of a maximum score of 100. All three sustainability dimensions of the vegetable farms were, on average, at a low level and improvements were needed for them to reach an acceptable standard. The vegetable farms located in the south of Benin had, on average, a higher sustainability score than those in the north: around 50% of vegetable farms in the south had a medium score, while the sustainability level of almost 75% of vegetable farms in the north was low. Interventions seeking to improve the sustainability of vegetable farms in Benin should focus on the promotion and adoption of eco-responsible practices that improve on-farm biodiversity, water conservation, and the effective allocation and management of land and labor, to mitigate the environmental impacts of vegetable production.